"An automatic Bible in the brain": Trauma and prayer among Acholi Pentecostals in northern Uganda. (August 2021) - Williams, Lars H.
This article examines the role of prayers for traumatized survivors of war within a Pentecostal-charismatic community in post-conflict northern Uganda. It argues that becoming part of a church group and learning certain regimes of prayer can work toward symptom relief and recovery for people suffering from traumatic experiences. The study builds on 13 months of ethnographic fieldwork in rural northern Uganda, with extensive participant observation of religious practices and interviews with rural church congregants. The article attempts to show, through a single case narrative, how individual prayer practices are trained and learned and to identify features of prayer that may alter the individual experience of distress. Analytically, the article builds on Tanya Luhrmann's scholarship on prayer and applies this conceptual framework to a post-conflict context. The study expands on Luhrmann's concepts of prayer as an emotional technology in order to understand how psychiatric symptoms are managed within a Pentecostal-charismatic community. The article further argues that a conceptual focus on training of skills can contribute to debates on the universal versus particular characteristics of psychiatric expression and concepts of mind. This argument contributes to current debates on non-clinical ways of managing traumatic experiences and to debates about models of mind in different cultural settings.